Treatment of polypropylene microfibers by atmospheric and low-pressure plasma – application to a reinforced cement composite containing recycled concrete - Jakub Ďureje; Zdeněk Prošek; Jan Trejbal; Štěpán Potocký; Radim Hlůžek (Acta Polytechnica CTU Proceedings, 2023)
The effect of atmospheric and low-pressure plasma modification on polypropylene (PP) microfibers was examined. Mechanical changes on the microfiber surfaces were observed using scanning electron microscopy (SEM). Next, wettability was measured using the packed-cell method. The fibers were applied into a cement matrix containing micro-milled recycled concrete. Test specimens were made and then the dynamic modulus of elasticity was continuously measured. After 28 days were made in the test specimens central notches to a depth of 14 mm. Finally, bending tests were performed. From the results, the fracture energy of the composite material was calculated. It was proven that low-pressure plasma modification as well as atmospheric plasma modification increases the wettability of PP fibers with water. Furthermore, it was found that samples containing plasma-modified microfibers have a higher fracture energy compared to the same samples with fibers without plasma modification. Conversely, plasma modification had no effect on the dynamic modulus of elasticity.